The food allergy in medical practice - Bartuzi, Zbigniew (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2009)
The food protein triggering the allergic response is termed a food allergen. Six to eight percent of children under the age of three have food allergies and nearly four percent of adults have them. The most common food allergies in adults are shellfish, peanuts, tree nuts, fish, and eggsand the most common food allergies in children are milk, eggs, peanuts, and tree nus. Conditions caused by food allergies are classified into 3 groups according to the mechanism of the allergic response. The reaction may progress to anaphylactic shock: a systemic reaction involving several different bodily systems including hypotension (low blood pressure), loss of consciousness, and possibly death. Allergens most frequently associated with this type of reaction are peanuts, nuts, milk, egg, and seafood, though many food allergens have been reported as triggers for anaphylaxis. Food allergy is thought to develop more easily in patients with the atopic syndrome, a very common combination of diseases: allergic rhinitis and conjunctivitis, eczema and asthma. The syndrome has a strong inherited component, a family history of allergic diseases can be indicative of the atopic syndrome. Article is still standing with the attempt to move connected with the undesirable effect of sustenance, observed in the daily medical practice based on problems closer knowledge.